2018
DOI: 10.14419/ijet.v7i2.11247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of The Building Maintenance and Resource Management Through User Satisfaction of Maintenance

Abstract: PD Pasar Jaya manages 153 markets spread across Jakarta. Market building is a place of public services, in order to provide excellent service to the community, it is important to maintain it properly. Maintenance management of PD Pasar Jaya is still far from the expected. The purpose of this study was to determine the effect of directly and indirectly from the condition of the building and maintenance resources to user satisfaction through maintenance management. The research method is by taking a sample of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…According to Zalejska-Jonsson [36], in addition to building severity, the level of comfort felt by building occupants is also one of the determinants of building quality. Pontan et al [37] also showed that 68.65% of building maintenance effectiveness is affected by building occupant satisfaction. However, the Department of Civil Engineering did not carry out the survey.…”
Section: Building Maintenance Documentsmentioning
confidence: 99%
“…According to Zalejska-Jonsson [36], in addition to building severity, the level of comfort felt by building occupants is also one of the determinants of building quality. Pontan et al [37] also showed that 68.65% of building maintenance effectiveness is affected by building occupant satisfaction. However, the Department of Civil Engineering did not carry out the survey.…”
Section: Building Maintenance Documentsmentioning
confidence: 99%
“…In this sense, maintenance strategies can take advantages of control-based (or rather, "cognitive") approaches, such as those related to: 1) BAS and internet of things (IoT)-based technologies [10,25]; 2) direct communication from and to the users and the professionals within the maintenance team [19,26]. BAS can manage data on the condition of the components, especially for those that can be directly and remotely monitored (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Then, "Building Automation Systems" (BAS) could be connected to such models to support building stakeholders in adopting proper O&M strategies [10,11,17]. Finally, a direct "interaction with the users" can be useful to increase their awareness, to lead them to perform "proper" behaviors and to rise their satisfaction level in the building use [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…comfort, safety, management of spaces and flows) [1,2]. In fact, users are subjected to boundary conditions (physical, social, psychological) which can vary over time and space: they face such conditions by adapting their behaviours to increase their considered space [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Infatti, gli utenti sono sottoposti a condizioni al contorno (di tipo fisico, sociale, psicologico) variabili nel tempo e nello spazio, e che fronteggiano adattando le loro azioni per aumentare il proprio livello di soddisfazione. Così facendo, essi possono interagire con lo spazio fisico e i componenti edilizi, modificandone lo stato e quindi, di conseguenza, le condizioni ambientali e, infine, le performance dell'edificio [3]- [6]. Gli Spazi Architettonici (sia indoor che outdoor) possono utilizzare approcci di tipo "cognitivo" per permettere al costruito di adattarsi ai bisogni degli utenti sulla base della combinazione tra condizioni ambientali e comportamenti attuati dagli occupanti, sia in condizioni ordinarie sia di emergenza [7]- [9].…”
Section: Introduzioneunclassified